A two-step binding mechanism for the self-binding peptide recognition of target domains. Issue 4 (8th February 2016) - Yang, Chao; Zhang, Shilei; Bai, Zhengya; Hou, Shasha; Wu, Di; Huang, Jian; Zhou, Peng
Abstract : By using state-of-the-art molecular dynamics to reconstruct the complete structural dynamics picture of self-binding peptides, a two-step binding mechanism was proposed, including a fast, nonspecific diffusive phase and a slow, specific organizational phase. Abstract : Self-binding peptides (SBPs) represent a novel biomolecular phenomenon spanning between folding and binding, where a short peptide segment within a monomeric protein fulfills biological functions by dynamically binding to/unbinding from its target domain in the same monomer. Here, we were able to quantitatively reconstruct the complete structural dynamics picture of binding of free SBPs to their target domains for five representative SBP systems by carrying out the state-of-the-art molecular dynamics (MD) simulations. In the picture, a two-step binding mechanism for SBP–domain recognition and association was proposed, which includes a fast, nonspecific diffusive phase and a slow, specific organizational phase. The electrostatic interactions and desolvation effects play a predominant role in the first phase that leads to the formation of a metastable encounter complex, while conformational rearrangement is observed in the second phase to optimize the exquisite network of nonbonded chemical forces such as hydrogen bonds and salt bridges across the complex interface. From an energetic point of view, a funnel-shape enthalpy landscape steers these SBPs towards their native bound state and thus facilitates the binding process. However, the binding exhibits typical enthalpy–entropy compensation due to the high flexibility of peptides that results in a relatively low affinity for SBP–domain binding and forces the SBP systems to rapidly switch between the bound and unbound states. In addition, slight conformational changes in the target domain and/or in the polypeptide linker between the domain and peptide can significantly affect the energetic properties and dynamic behavior of the fine-tuned binding process of SBP–domain recognition.